Nanofibrous scaffolds for regenerative endodontics treatment - Huang, Fangting; Cheng, Lei; Li, Jiyao; Ren, Biao (Frontiers in Bioengineering and Biotechnology, 2022)
Untreated dental caries, tooth trauma and dental anatomical variations such as dens invaginatus can result in pulpitis. However, standard root canal therapy cannot treat immature permanent teeth due to an open apical foramen and thin dentinal walls. Thus, regenerative endodontics treatment (RET) following a disinfection step with pulp regeneration has been developed. Pulp connective-tissue, dentin formation, revascularization and reinnervation can occur in this procedure which should be supplemented with intelligent biomaterials to improve repeatability and support well-coordinated regeneration. Furthermore, nanofibrous scaffolds, as one of the most commonly used materials, show promise. The purpose of this article is to highlight the advantages of nanofibrous scaffolds and discuss the future modification and application of them.